Proses Interpretasi Siswa SMP dalam Menyelesaikan Masalah Numerasi - Bunga Cahyaning Atie; Abdul Haris Rosyidi (Program Studi S1 Matematika UNESA, 2023)
The interpretation process is the process of interpreting the problem, information in the form of a representation, and communicating the proposed interpretation according to the context of the problem. Interpretation plays a role in solving numeracy problems, namely by analyzing information, predicting, and making decisions in solving problems. This research is a qualitative research with the aim of describing the interpretation process of junior high school students in solving numeracy problems. The research subjects were three grade VIII students of SMP Negeri in Surabaya, taking into account the various interpretations of students. Data on students' interpretation processes in solving numeracy problems were obtained through task-based interviews and analyzed using indicators of the interpretation process in solving numeration problems. The results showed that each student had read the graphs provided, and compared the two graphs by determining the differences and similarities between the two graphs. Students analyze the relationship between variables by associating information on graphs and student experiences. The results of the conclusions of each student vary due to the different interpretations of students on graphs. In presenting arguments students have difficulty with questions that require steps and evidence in drawing conclusions. Students check the correct interpretation of information and questions in problems by reflecting on solutions to questions and student experiences.